Samarium enriches antitumor activity of ZnO nanoparticles via downregulation of CXCR4 receptor and cytochrome P450 - Asmaa I Nabeel (Tumor Biology, 2020)
Cancer is the leading cause of death and exhausts human and economic resources for treatment and protection. Zinc oxide nanoparticles play an effective role in tumor treatment but with some cautions, such as overexpression of cytochrome P450, hepatic overload, and the mammalian target of rapamycin pathway resistance. Although lanthanides have antitumor activity, their use is limited. Therefore, the current study aims to improve the effectiveness of zinc oxide nanoparticle via doping with lanthanides, such as samarium. In vitro study revealed that samarium doped with zinc oxide showed more antitumor activity than the other lanthanides, and the antitumor activity depends on the concentration of samarium in the nanocomposite. The in vivo experiment on mice bearing Ehrlich solid tumor revealed that intramuscular injection of samarium/zinc oxide downregulates the expressions of CXCR4 and PI3K/Akt/mammalian target of rapamycin pathway in respect to Ehrlich solid tumor group. Regarding the apoptotic biomarkers, samarium/zinc oxide upregulates the apoptotic biomarker; Bax accompanied with the mitotic catastrophe which was indicated by cell cycle arrest in G2 phase. Moreover, samarium:zinc oxide nanoparticles exhibited minimum toxicity which was indicated by suppressed activities of cytochrome P450 and hepatic enzymes, including alanine transaminase and aspartate transaminase. In addition, the histopathological finding, as well as immunophenotyping results, appreciated the biochemical finding. Therefore, samarium:zinc oxide might be offered a new approach to improve the effectiveness of zinc oxide nanoparticles along with lower toxic effect. Also, samarium:zinc oxide nanoparticles can be a candidate as a new antitumor compound to detect its mode of action.